Modern Development and Production of a New Live Attenuated Bacterial Vaccine, SCHU S4 ΔclpB, to Prevent Tularemia - J. Wayne Conlan; Anders Sjöstedt; H. Carl Gelhaus; Perry Fleming; Kevan McRae; Ronald R. Cobb; Roberto De Pascalis; Karen L. Elkins (Pathogens, 2021)
Inhalation of small numbers of Francisella tularensis subspecies tularensis (Ftt) in the form of small particle aerosols causes severe morbidity and mortality in people and many animal species. For this reason, Ftt was developed into a bona fide biological weapon by the USA, by the former USSR, and their respective allies during the previous century. Although such weapons were never deployed, the 9/11 attack quickly followed by the Amerithrax attack led the U.S. government to seek novel countermeasures against a select group of pathogens, including Ftt. Between 2005–2009, we pursued a novel live vaccine against Ftt by deleting putative virulence genes from a fully virulent strain of the pathogen, SCHU S4. These mutants were screened in a mouse model, in which the vaccine candidates were first administered intradermally (ID) to determine their degree of attenuation. Subsequently, mice that survived a high dose ID inoculation were challenged by aerosol or intranasally (IN) with virulent strains of Ftt. We used the current unlicensed live vaccine strain (LVS), first discovered over 70 years ago, as a comparator in the same model. After screening 60 mutants, we found only one, SCHU S4 ΔclpB, that outperformed LVS in the mouse ID vaccination-respiratory-challenge model. Currently, SCHU S4 ΔclpB has been manufactured under current good manufacturing practice conditions, and tested for safety and efficacy in mice, rats, and macaques. The steps necessary for advancing SCHU S4 ΔclpB to this late stage of development are detailed herein. These include developing a body of data supporting the attenuation of SCHU S4 ΔclpB to a degree sufficient for removal from the U.S. Select Agent list and for human use; optimizing SCHU S4 ΔclpB vaccine production, scale up, and long-term storage; and developing appropriate quality control testing approaches.